Lentog Tanjung: Antara Tradisi Kuliner dan Tantangan Modernisasi di Era Globalisasi di Abad 20 - Naia Sophianti; Muzakki Bashori (Universitas Negeri Semarang, 2024)
Lentog Tanjung is a traditional culinary dish unique to Kudus, Indonesia, with deep historical and cultural roots. This article examines Lentog Tanjung from historical, preparation, and cultural value perspectives. The main focus is to assess how modernization and globalization affect the sustainability of this culinary tradition. By exploring traditional ingredients, cooking techniques, and the social and cultural roles of Lentog Tanjung, the article highlights the challenges faced in preserving the authenticity of this dish amid changing lifestyles. Efforts for preservation by local communities, government, and business actors, as well as the role of the younger generation in maintaining and developing Lentog Tanjung, are also discussed. The article evaluates the potential for developing Lentog Tanjung as a culinary product within the creative economy and tourism, alongside innovative strategies to expand market reach.